2014
DOI: 10.1007/s00264-014-2574-9
|View full text |Cite
|
Sign up to set email alerts
|

Femoroacetabular impingement syndrome—efficacy of surgical treatment with regards to age and basic diagnosis

Abstract: The results of the study affirm the relevance of hip preserving surgery, especially in younger-aged groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, it is yet not clear whether FAI represents a normal variant in older patients or whether it is a condition associated with severe and aggressive arthritis even in older patients. Because some studies describe surgical interventions for FAI not only for young athletes, but also for older people [13,41,54], it is important to study patients of all ages who have radiographic signs of FAI and also to evaluate the association of FAI with pain and arthrosis in an older community-based cohort. We found that radiographic signs of FAI are common in older men and that the different types of FAI were not associated with increased pain and in fact that patients with cam-type FAI had a slightly lower risk of pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is yet not clear whether FAI represents a normal variant in older patients or whether it is a condition associated with severe and aggressive arthritis even in older patients. Because some studies describe surgical interventions for FAI not only for young athletes, but also for older people [13,41,54], it is important to study patients of all ages who have radiographic signs of FAI and also to evaluate the association of FAI with pain and arthrosis in an older community-based cohort. We found that radiographic signs of FAI are common in older men and that the different types of FAI were not associated with increased pain and in fact that patients with cam-type FAI had a slightly lower risk of pain.…”
Section: Discussionmentioning
confidence: 99%
“…In young adults, FAI can be associated with severe arthroscopic degeneration of the hip, whereas in older age groups, it can be a normal variant. In addition, there are now a number of reports that describe surgery for FAI in older people (older than 50 years of age) [7,13,26,41]. Therefore, it is critical to study the complete spectrum of FAI, including in older patients, as well as its association with pain and arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…13 The two main reasons cited to support surgical intervention are the correction of morphological changes and the prevention of intra-articular injury. 14 However, the number of randomized controlled trials of high methodological quality that support the effectiveness of surgery for femoroacetabular impingement syndrome is limited. 15,16 Therefore, it is suggested that clinicians and patients should be cautious when choosing approaches, and non-surgical treatment should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological correction and prevention of hip osteoarthritis are 2 primary reasons given to support surgical intervention. 9 Improvement of motor control and strengthening of the dynamic stabilizing muscles of the hip and pelvis provide a rationale for nonsurgical treatment. 7,27,53,54…”
mentioning
confidence: 99%